Exploring the effect of estrogen on Candida albicans hyphal cell wall glycans and ergosterol synthesis - Bataineh, Mohammad Tahseen AL; Cacciatore, Stefano; Semreen, Mohammad Harb; Dash, Nihar Ranjan; Soares, Nelson C.; Zhu, Xiaolong; Mousa, Muath Khairi; Salam, Jasmin Shafarin Abdul; Zerbini, Luiz F.; Hajjo, Rima; Hamad, Mawieh (Frontiers in Cellular and Infection Microbiology, 2022)
Increased levels of 17-β estradiol (E2) due to pregnancy in young women or to hormonal replacement therapy in postmenopausal women have long been associated with an increased risk of yeast infections. Nevertheless, the effect underlying the role of E2 in Candida albicans infections is not well understood. To address this issue, functional, transcriptomic, and metabolomic analyses were performed on C. albicans cells subjected to temperature and serum induction in the presence or absence of E2. Increased filament formation was observed in E2 treated cells. Surprisingly, cells treated with a combination of E2 and serum showed decreased filament formation. Furthermore, the transcriptomic analysis revealed that serum and E2 treatment is associated with downregulated expression of genes involved in filamentation, including HWP1, ECE1, IHD1, MEP1, SOD5, and ALS3, in comparison with cells treated with serum or estrogen alone. Moreover, glucose transporter genes HGT20 and GCV2 were downregulated in cells receiving both serum and E2. Functional pathway enrichment analysis of the differentially expressed genes (DEGs) suggested major involvement of E2 signaling in several metabolic pathways and the biosynthesis of secondary metabolites. The metabolomic analysis determined differential secretion of 36 metabolites based on the different treatments’ conditions, including structural carbohydrates and fatty acids important for hyphal cell wall formation such as arabinonic acid, organicsugar acids, oleic acid, octadecanoic acid, 2-keto-D-gluconic acid, palmitic acid, and steriacstearic acid with an intriguing negative correlation between D-turanose and ergosterol under E2 treatment. In conclusion, these findings suggest that E2 signaling impacts the expression of several genes and the secretion of several metabolites that help regulate C. albicans morphogenesis and virulence.